2021
DOI: 10.1177/03000605211040263
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the recovery time of patients with coronavirus disease 2019 using an accelerated failure time model

Abstract: Objective To identify factors associated with recovery time from coronavirus disease 2019 (COVID-19). Methods In this retrospective study, data for patients with COVID-19 were obtained between 21 June and 30 August 2020. An accelerated failure time (AFT) model was used to identify covariates associated with recovery time (days from hospital admission to discharge). AFT models with different distributions (exponential, log-normal, Weibull, generalized gamma, and log-logistic) were generated. Akaike’s informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…In these models, median survival times and also TR rather than HR are calculated [ 19 ] . The TR greater than one denotes that the effect of a covariate prolongs survival time and TR less than one denotes a shorter survival time [ 23 ] . In survival analysis, AFT models have widely been used to model diseases, including acute liver failure, leukemia, thalassemia, and cancers [ 24 , 25 ] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these models, median survival times and also TR rather than HR are calculated [ 19 ] . The TR greater than one denotes that the effect of a covariate prolongs survival time and TR less than one denotes a shorter survival time [ 23 ] . In survival analysis, AFT models have widely been used to model diseases, including acute liver failure, leukemia, thalassemia, and cancers [ 24 , 25 ] .…”
Section: Introductionmentioning
confidence: 99%
“…In survival analysis, AFT models have widely been used to model diseases, including acute liver failure, leukemia, thalassemia, and cancers [ 24 , 25 ] . These models have also been applied to determine factors such as recovery time, hospital discharge, intubation periods, and the serial intervals of COVID-19 cases [ 23 , 26 , 27 ] . However, limited studies have been focused on investigating the relationship of at admission Hb levels at admission with COVID-19 mortality [ 3 , 28 ] , and this problem is still insufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…The mean pre-symptomatic period, 1/c, is assumed to be 2.9 (7). The mean duration of infectiousness for symptomatic individuals (1/f) is 15.7 days, and that of asymptomatic individuals (1/q) is 7.25 days (8)(9)(10)(11). The transmission rate, β, is estimated from the basic reproduction number (R0) using the formula (1 − 𝛿𝛿) � 𝑢𝑢𝛽𝛽 𝑞𝑞 � + 𝛿𝛿( 𝑟𝑟𝛽𝛽 𝑐𝑐 + 𝛽𝛽 𝑓𝑓 ) (12), assuming a value of 3.13 for the initial strain as assessed by Armachie and colleagues (13).…”
Section: Model Parametersmentioning
confidence: 99%
“…Hence, the government's goal to reach widespread vaccine coverage by October 2021 was not met (6). Studies on COVID-19 vaccine hesitancy among Ghanaians reported that more than 35% of participants said they would not receive the vaccine because of concerns about vaccine efficacy and conspiracy theories (7,10). Moreover, a seroprevalence study found that 19% of Ghanaians tested positive to anti-SARS-CoV-2 IgM or IgG or both in August 2020 (11).…”
Section: Main Text (3412 Max Words=3500) Introductionmentioning
confidence: 99%
“…31 The mean duration of infectiousness is 15.7 days (95% CI: 13, 18.4) and 7.25 days (95% CrI: 5.1, 8.69) for symptomatic individuals (1/f) and asymptomatic individuals (1/h), respectively. [32][33][34][35] The transmission coefficient, β, is estimated from the basic reproduction number (R0), which is assumed to be 3.13 (95% CrI: 1.24, 6.35) as reported by Armachie and colleagues for the initial strain in Ghana. 36 According to the Centers for Disease Control and Prevention (CDC) COVID-19 pandemic planning scenarios, the relative transmissibility of asymptomatic and presymptomatic individuals, u and r, are assumed to be 0.75, respectively.…”
Section: Model Parametersmentioning
confidence: 99%